Central regions of keloids are severely ischaemic. Issue 2 (February 2016) - Touchi, Ryoma; Ueda, Koichi; Kurokawa, Norifumi; Tsuji, Motomu
Summary: We classified scars as keloids, hypertrophic scars and mature scars, and then examined the scars for differences in central and marginal vascularization. We found significant differences in localized hypoxia-induced factor-1α (HIF-1α) expression and vascular density in keloids, but no localized differences in hypertrophic or mature scars. The central areas of keloids exhibited higher HIF-1α expression and lower vascular density than marginal areas, suggesting that the former are severely ischaemic.